Edukasi Hubungan Stunting terhadap Faktor Resiko Penyakit Tidak Menular pada Gen Z di SMAN 10 Medan - Pratiwi, Dian; Panduwati, Digna Renny; Wahyuni, Sri (Jurnal Pengabdian Masyarakat Akademisi, 2025)
Stunting is caused by various factors, primarily nutritional intake during the first 1,000 days of life. Stunting has significant impacts on children's health and can hinder Indonesia's demographic bonus in the future by affecting the competitiveness of its productive human resources. All parties are expected to care and take action in the effort to prevent stunting in children, including adolescents, who are part of Generation Z and the successors of the millennial generation. This topic was chosen to educate Gen Z about the relationship between stunting and the risk factors for non-communicable diseases. The method used involved administering questionnaires to assess participants’ understanding before and after the educational intervention. The results showed an increase in Gen Z's knowledge from 14% to 74%. In terms of health screening outcomes, 90% had normal blood pressure and 72% had normal blood glucose levels.